Sodium Butyrate Reduces Salmonella Enteritidis Infection of Chicken Enterocytes and Expression of Inflammatory Host Genes in vitro - Gupta, Anamika; Bansal, Mohit; Wagle, Basanta; Sun, Xiaolun; Rath, Narayan; Donoghue, Annie; Upadhyay, Abhinav (Frontiers in Microbiology, 2020)
Salmonella Enteritidis (SE) is a facultative intracellular pathogen that colonizes the chicken gut leading to contamination of carcasses during processing. A reduction in intestinal colonization by SE could result in reduced carcass contamination thereby reducing the risk of illnesses in humans. Short chain fatty acids such as butyrate are microbial metabolites produced in the gut that exert various beneficial effects. However, its effect on SE colonization is not well known. The present study investigated the effect of sub-inhibitory concentrations (SICs) of sodium butyrate on the adhesion and invasion of SE in primary chicken enterocytes and chicken macrophages. In addition, the effect of sodium butyrate on the expression of SE virulence genes and selected inflammatory genes in chicken macrophages challenged with SE were investigated. Based on the growth curve analysis, the two SICs of sodium butyrate that did not reduce SE growth were 22 and 45 mM, respectively. The SICs of sodium butyrate did not affect the viability and proliferation of chicken enterocytes and macrophage cells. The SICs of sodium butyrate reduced SE adhesion by ∼1.7 Log CFU/mL and ∼1.8 Log CFU/mL respectively. The SE invasion was reduced by ∼2 Log CFU/mL and ∼2.93 Log CFU/mL respectively in chicken enterocytes (P<0.05). Sodium butyrate did not significantly affect the adhesion of SE to chicken macrophages. However, 45 mM sodium butyrate reduced invasion by ∼1.7 Log CFU/mL as compared to control (P<0.05). Exposure to sodium butyrate did not change the expression of SE genes associated with motility (flgG, prot6E), invasion (invH), type 3 secretion system (sipB, pipB), survival in macrophages (spvB, mgtC), cell wall and membrane integrity (tatA), efflux pump regulator (mrr1) and global virulence regulation (lrp) (P>0.05). However, a few genes contributing to type-3 secretion system (ssaV, sipA), adherence (sopB), macrophage survival (sodC) and oxidative stress (rpoS) were upregulated by at least 2 folds. The expression of inflammatory genes (Il1β, Il8 and Mmp9) that are triggered by SE for host colonization was significantly downregulated (at least 25 folds) by sodium butyrate as compared to SE (P<0.05). The results suggest that sodium butyrate has an anti-inflammatory potential to reduce SE colonization in chickens.